521 Farm animal welfare: Maintaining public trust and social acceptability. - von Keyserlingk, M (J Anim Sci, 2018)
Animal welfare is emerging as a key area of social concern in agriculture, such that we see increased public interest in how animals are housed and cared for on farms. Those working within agriculture sometimes believe that these concerns are mostly or entirely rooted in public ignorance of the practices, motivations and constraints faced by farmers, and thus believe that criticisms can be addressed through better public education. However, an ever-decreasing proportion of society works within the animal industries and it seems unlikely that efforts to ‘educate’ the public on these issues will often be successful. Moreover, the famers themselves are part of the rapid changes in societal views, and practices that were accepted by past generations may seem out of step for the next generation. To be sustainable in the long term the inclusion of societal input is needed for food animal production industries to retain their social license to operate. During this talk we highlight some of the contentious issues within the farm animal industries that are at risk of being out of step with societal values and possible solutions that may help pave the way forward in how we care and house farm animals.